HUBUNGAN LOCUS OF CONTROL INTERNAL DAN KECERDASAN ADVERSITAS DENGAN KESIAPAN KERJA SISWA KELAS XII PROGRAM KEJURUAN TEKNIK INSTALASI TENAGA LISTRIK DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 34 JAKARTA - Fajar Arif Budi Surahman; Suyitno; Parjiman (Fakultas Teknik Universitas Negeri Jakarta, 2021)
This study aims to determine: (1) Correlation between internal locus of control with work readiness, (2) Correlation between adversity quotient with work readiness, (3) Correlation between internal locus of control and adversity quotient with work readiness student of class XII TITL at SMK Negeri 34 Jakarta. The population of respondents is student of class XII TITL at SMK Negeri 34 Jakarta. The sampling technique uses a type of non-probability sampling that is saturated sampling technique, the research sample is students of class XII TITL 1 and TITL 2, total 61 students. Data collection using a questionnaire / questionnaire. The results of the analysis prerequisite analysis say that the research data are linear and normally distributed. Testing the research hypothesis using the product moment correlation test. The results of testing this research hypothesis can be seen from the correlation value ryx1 = 0.664, ryx2 = 0.665, ryx1x2 = 0.722 with rtable = 0.252 (rcount> rtable 5%), meaning that the research hypothesis can be said to prove that (1) there is a positive correlation between locus of control internal with work readiness, (2) there is a positive correlation between adversity quotient and work readiness, (3) there is a positive correlation between internal locus of control and adversity quotient simultaneously with work readiness student of class XII TITL at SMK Negeri 34 Jakarta. With this result, it can be concluded that the higher the level of internal locus of control and the quotient of student adversity, the work readiness that will be possessed by students of class XII of the Electrical Power Installation Engineering Program at SMK Negeri 34 Jakarta will also be high. Abstrak Penelitian ini bertujuan untuk mengetahui (1) Hubungan locus of control internal dengan kesiapan kerja, (2) Hubungan kecerdasan adversitas dengan kesiapan kerja, (3) Hubungan locus of control internal dan kecerdasan adversitas dengan kesiapan kerja siswa kelas XII TITL di SMK Negeri 34 Jakarta. Populasi responden adalah siswa kelas XII TITL di SMK Negeri 34 Jakarta. Teknik sampling menggunakan jenis non probability sampling yaitu teknik sampling jenuh, maka sampel penelitian adalah siswa kelas XII TITL 1 dan TITL 2 yang berjumlah 61 siswa. Pengumpulan data menggunakan kuisioner/angket. Hasil pengujan prasyarat analisis mengatakan bahwa data penelitian bersifat linear dan berdistribusi normal. Pengujian hipotesis penelitian menggunakan uji korelasi product moment. Hasil pengujian hipotesis penelitian ini terlihat dari nilai korelasi ryx1= 0,664, ryx2= 0,665, ryx1x2= 0,722 dengan rtabel= 0,252 (rhitung > rtabel 5%), artinya hipotesis penelitian dapat dikatakan terbukti bahwa (1) terdapat hubungan yang positif antara locus of control internal dengna kesiapan kerja, (2) terdapat hubungan yang positif antara kecerdasan adversitas dengan kesiapan kerja, (3) terdapat hubungan yang positif antara locus of control internal dan kecerdasan adversitas secara simultan dengan kesiapan kerja siswa kelas XII TITL SMK Negeri 34 Jakarta. Dengan hasil ini, maka didapatkan kesimpulan bahwa semakin tinggi tingkat locus of control internal dan kecerdasan adversitas siswa maka kesiapan kerja yang akan dimiliki siswa kelas XII Program Kejuruan Teknik Instalasi Tenaga Listrik di SMK Negeri 34 Jakarta juga akan tinggi.